The influence of in ovo feeding of black cumin extract on the physiological responses of broilers under hot tropical environments - Omolayo Bose Oyelola; Oluwaseun Serah Iyasere; Oluwagbemiga Olanrewaju Adeleye; Oyegunle Emmanuel Oke (Acta Scientiarum. Animal Sciences, 2023)
An experiment was conducted to investigate the influence of in ovo feeding of black cumin extract (BC) on the intestinal morphology and physiological responses of broilers thermally challenged during incubation. The study involved the use of seven hundred Marshall broiler hatching eggs, which were assigned to 7 in ovo feeding treatments at embryonic day 17.5, as follows: eggs injected with 8 mg (EN), 6 mg (SN), 4 mg (FN), 2 mg (TN)BC, no in ovo feeding (NI), 0.9 % saline solution (SS), and 3 mg vitamin C (VC). Juvenile growth performance, plasma malondialdehyde (MDA), triiodothyronine (T3), superoxide dismutase (SOD), and haematological and serum biochemical indices were evaluated. The results revealed that the juvenile growth performance of SN birds was better than those of the NI, SS, FN and TN groups. The plasma SOD and T3 of the birds of SN and VC were significantly higher (p < 0.05) than the chickens of NI and SS treatments. The ileal crypt depth recorded in SN birds was lower (p < 0.05) compared to SS and NI values. To conclude, in ovo black cumin extract enhanced the gut health and lymphoid organs of broiler chickens with no pronounced effect on the thermotolerance of the birds at market age.